Magnolia Table, V 2: A Collection of Recipes for Gathering Volume 2 - Gaines, Joanna 1978-; Neunsinger, Amy (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2020)
"At the end of the day, it's gathering around the table and sharing a meal with the ones you love that make time spent in the kitchen worthwhile"--Back cover.
The art of gathering -- Guide to herbs, seasonings & substitutions -- Scratch made -- Breads -- Breakfast & brunch -- Soups & salads -- Appetizers & starters -- Side dishes -- Dinner -- Desserts.
Keywords: Cooking, American -- Southern style; Cookbooks